Integrasi Sistem Pembelajaran dengan Google Classroom melalui Google Apps Script - Sopingi Sopingi; Septi Wulandari (Justek : Jurnal Sains dan Teknologi, 2023)
Abstract: Learning is a science communication activity between educators and students that can run in blended learning. One of the learning platforms that can be used is Google Classroom which requires adequate preparation, management and readiness of information technology. The purpose of this research is to develop academic system integration, especially in learning features with the Google Classroom platform through Google Apps Script with response time performance and good use of server resources. This study uses the Rational Unified Process (RUP) method approach with an object oriented concept. The results of the research are in the form of a school academic system that has integrated learning system features with Google Classroom. The results of the response time performance test obtained an average value of 3,364 ms while the average memory usage on the server was 16.17M. So it was concluded that the use of Google Apps Script has less efficient performance.Abstrak: Pembelajaran merupakan kegiatan komunikasi ilmu pengetahuan antara pendidik bersama peserta didik yang dapat berjalan secara blended learning. Salah satu platform pembelajaran yang dapat digunakan adalah Google Classroom yang membutuhkan persiapan, pengelolaan dan kesiapan teknologi informasi yang memadai. Tujuan dari penelitian ini adalah pengembangan integrasi sistem akademik khususnya pada fitur pembelajaran dengan platform Google Classroom melalui Google Apps Script dengan performa response time dan penggunaan resource server yang baik. Penelitian ini menggunakan pendekatan metode Rational Unified Process (RUP) dengan konsep object oriented. Hasil penelitian berupa sistem akademik sekolah yang memiliki fitur sistem pembelajaran terintegrasi denga Google Classroom. Hasil pengujian performa response time didapatkan nilai rata-rata 3.364 ms sedangkan rata-rata penggunaan memory pada server sebesar 16,17M. Maka disimpulkan penggunaan Google Apps Script memiliki performa kurang efisien